Lower Back Pain as an Occupational Hazard Among Ugandan Health Workers - Aleku, Michael; Nelson, Kevin; Abio, Anne; Lowery Wilson, Michael; Lule, Herman (Frontiers in Public Health, 2021)
Background: Lower back pain is a public health concern affecting 70–85% of the world's population. There is paucity of published data on the prevalence, disability and risk factors for lower back pain among health workers in Uganda. Objective: To determine the frequency rate (note that is it implicit that frequency is a rate like incidence so including rate seems redundant here. This is bounded by zero and infinity. In contrast, prevalence is bounded by 0 and 1 and is thus a proportion not a rate) of lower back pain and its associated risks amongst health professionals in the Arua District of Uganda. Methods: Cross-sectional descriptive study of 245 consecutive participants conducted during February-April 2020. We stratified risks as individual or work related and analyzed the data using IBM SPSS version 25. Chi-square was used to measure the significance of association between categorical variables at 95% confidence interval, regarding a p ≤ 0.05 as significant. Results: The mean age of participants was 40.87 years ± 8.74 (SD), with female predominance (69.8%). Majority were either general nurses or midwives (64.9%) and more than half had practiced for over 6–10 years. The frequency rate of lower back pain was 39.6% (n = 97). Individual factors associated with LBP were; cigarette smoking (X2 = 33.040; P ≤ 0.001), alcohol consumption (X2 = 13.581; P ≤ 0.001), age (X2 = 14.717; P = 0.002), and female gender (X2 = 4.802; P = 0.028). The work related factors significantly associated with lower back pain were: being a nurse/midwife (X2 = 9.829; P = 0.007), working in the outpatient department (X2 = 49.752; P ≤ 0.001), bending (X2 = 43.912; P ≤ 0.001), lifting (X2 = 33.279; P < 0.001), over standing (X2 = 40.096; P ≤ 0.001), being in awkward positions (X2 = 15.607; P= < 0.001), and pushing patients (X2 = 21.999; P ≤ 0.001). Conclusion: The frequency rate of low back pain was high amongst health workers and its main associated individual and work related factors could have been prevented. Health workers should strike a balance between caring for their personal back-health and meeting clients' needs while manually handling patients. Ergonomic structuring, job organization, back health care courses and use of assistive equipment could reduce such occupational hazards in our low resourced settings.